Antimicrobial Stewardship in Bronchiolitis: A Retrospective Cohort Study of Three PICUs in Canada. Issue 3 (March 2022) - Aljassim, Nada A.; Noël, Kim C.; Maratta, Christina; Tam, Ingrid; Almadani, Ahmed; Papenburg, Jesse; Quach, Caroline; Thampi, Nisha; McNally, James D.; Dendukuri, Nandini; Lefebvre, Marie-Astrid; Zavalkoff, Samara; et al.
Abstract : OBJECTIVES: To determine the association between the implementation of an antimicrobial stewardship program at a local PICU and to determine the association between the presence of an antimicrobial stewardship programs and antimicrobial use across three Canadian PICUs, among critically ill children with bronchiolitis. DESIGN: A multicenter retrospective cohort study. SETTING: Three Canadian PICUs over two winter seasons. INTERVENTIONS: An antimicrobial stewardship program was implemented at PICU 1 at the end of season 1. PATIENTS: Patients less than or equal to 2 years old admitted with bronchiolitis. MEASUREMENTS AND MAIN RESULTS: We used regression models with an interaction term between site (PICU 1 and PICU 2) and season (1 and 2) as the primary analysis to determine the association between implementation of an antimicrobial stewardship program at PICU 1 and 1) the proportion of antimicrobials discontinued 72 hours after hospital admission (logistic regression), 2) antimicrobial treatment duration (negative binomial regression), and 3) antimicrobial prescriptions within 48 hours of hospital admission (logistic regression). As a secondary analysis, we determined the association between having an antimicrobial stewardship program present and the aforementioned outcomes across the three PICUs. A total of 372 patients were included. During seasons 1 and 2, median age was 2.2 months (interquartile range, 1.2–6.2 mo) and 2.1 months (interquartile range, 1.3–6.8 mo), respectively. Among patients with viral bronchiolitis, implementation of an antimicrobial stewardship program at PICU 1 was associated with increased odds of discontinuing antimicrobials (odds ratio, 25.63; 95% CI, 2.86–326.29), but not with antimicrobial duration (odds ratio, 0.56; 95% CI, 0.31–1.02) or antimicrobial prescriptions (odds ratio, 0.33; 95% CI, 0.10–1.04). The presence of an antimicrobial stewardship program was similarly associated with antimicrobial discontinuation among patients with viral bronchiolitis (odds ratio, 20.79; 95% CI, 2.46–244.92), but not with antimicrobial duration (odds ratio, 0.57; 95% CI, 0.32–1.03) or antimicrobial prescriptions (odds ratio, 0.37; 95% CI, 0.12–1.11). CONCLUSIONS: Antimicrobial stewardship programs were associated with increased likelihood of discontinuing antimicrobial treatments in the PICU patients with viral bronchiolitis. However, larger studies are needed to further determine the role of an antimicrobial stewardship programs in reducing unnecessary antimicrobial use in this patient population.